Isolated pulmonary cryptococcosis in a patient with Crohn's disease treated with infliximab: A case report and literature review. (2021) - Hussein, Mousa; Haq, Irfan Ul; Hameed, Mansoor; Alabbas, Abbas; Hadi, Hamad Abdel; Elarabi, Anam; Al-Bozom, Issam
Abstract: Tumor necrosis factor-alpha (TNF-α) inhibitors are widely used to treat various inflammatory conditions, where they have demonstrated excellent efficacy and tolerability. However, increased risk of infections is one of the most important concerns associated with these agents. Reactivation of tuberculosis and fungal infections have emerged as significant infective complications of anti-TNF-α therapy. Cryptococcus infection is an opportunistic fungal infection that can occur in patients receiving anti-TNF-α treatment. We report a rare case of isolated pulmonary cryptococcosis in a patient undergoing anti-TNF-α therapy for Crohn's disease. Our case should alert clinicians to the increased incidence and atypical presentation of pulmonary cryptococcosis in patients receiving anti-TNF-α treatment.